The Role of Forest Fires in Plant Biodiversity: Ecological Responses and Succession - Yiğit, Nurcan (Prensip Publishing, 2025)
Forest fires represent increasingly frequent disturbances in forested and semi-forested ecosystems, primarily driven by the interplay of natural processes and anthropogenic pressures. These events have reached alarming levels, significantly altering the structural, functional, ecological, and biological dynamics of forest ecosystems. Recognized as among the most destructive natural disturbances, forest fires exert direct and long-lasting effects on ecosystems that extend far beyond the mere burning of vegetation. This study aims to evaluate the ecological impacts of forest fires, with particular emphasis on their effects on floristic composition, the ecological responses of plant species, and the post-fire succession processes. Following fire events, substantial shifts in species diversity, dominance, and community structure are observed. The interplay between fire-resistant and fire-sensitive species plays a decisive role in shaping the trajectory of ecological succession. Moreover, the rapid proliferation of invasive species—often gaining a competitive edge in disturbed habitats—poses a serious threat to native plant diversity and overall ecosystem integrity. In this context, floristic monitoring studies are vital for informed conservation planning. Supporting natural succession, promoting the in situ conservation of native species, and implementing ecosystem-based management strategies emerge as critical tools for sustaining post-fire ecosystem resilience. This article adopts an interdisciplinary perspective to examine fire–flora interactions, synthesizing insights from the current literature and offering region-specific recommendations, particularly for forested ecosystems in Türkiye.